A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia - Levey, Brian (Zootaxa, 2016)
There have been a number of fairly recent papers dealing with Ovalisia Kerremans, 1900 under different generic or subgeneric names: Bílý (1993, as Pagdeniella Théry, 1935; 1997, as Ovalisia), Bílý et al. (2009, as Lamprodila (Ovalisia), Hołyński (2000, 2011a, 2011b, as Ovalisia). Hołyński (2011a, 2011b) has a number of misgivings over using the name Lamprodila Motschulsky 1860 for the genus containing the subgenus Ovalisia Kerremans, however as there does not appear to be any objective way to confirm or refute Hołyński’s views concerning Motschulsky’s intentions when he coined the name Lamprodila, I choose to follow the recent catalogues of Kubáň 2006 and Bellamy 2008 who treat Ovalisia Kerremans, 1900 as a subgenus of Lamprodila.